The influence of urban park types on vegetation characteristics and microclimate condition - Junis, Felixita (2019)
Global warming introduces meteorological hazards where it has caused the rising of air temperature, storm, flash flood and heat wave which were caused by greenhouse effects and forest loss due to the increasing population of humans. In order to satisfy human needs, more forest area needs to be cleared off where rapid urbanization has caused more vegetation replaced with sealed surfaces and built area. Thus, from this issue we can see how green spaces such as urban park play an important role in maintaining vegetation characteristics and modifying microclimate condition at urban areas. However, different types of urban parks have different influencing on the vegetation characteristics and microclimate condition because each type of urban park has its own landscape design and tree species selection. Therefore, this study aimed to determine the vegetation characteristics of different types of urban park; and to investigate the influence of different type of urban park on microclimate condition. This study was conducted at three different types of urban parks in Putrajaya which were forest based park, recreation based park and agriculture based park. The finding from this study has shown that the type of urban park did significantly influenced the vegetation characteristics and microclimate condition where each urban park had different air temperature, wind speed, relative humidity and solar radiation reduction. This study has shown that Taman Rimba Alam was significantly different in vegetation characteristics and microclimate condition compared to Taman Saujana Hijau and Taman Warisan Pertanian. For example, Taman Rimba Alam are able to reduce up to 2°C air temperature, 6% relative humidity, 0.1 m/s wind speed and 717 W/m2 solar radiation. Moreover, the findings from this study will be beneficial to urban park planner to have a proper planning in the future in deciding the type of urban park and how it can help in overcoming global warming. In addition, this study also shows that it is important to include shading factors in designing urban park for a cooler and comfortable condition.